2003
DOI: 10.1096/fj.02-0859fje
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond, high‐intensity pulsed electric fields induce apoptosis in human cells

Abstract: Electroporation by using pulsed electric fields with long durations compared with the charging time of the plasma membrane can induce cell fusion or introduce xenomolecules into cells. Nanosecond pulse power technology generates pulses with high-intensity electric fields, but with such short durations that the charging time of the plasma membrane is not reached, but intracellular membranes are affected. To determine more specifically their effects on cell structure and function, human cells were exposed to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
337
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 424 publications
(355 citation statements)
references
References 38 publications
11
337
1
Order By: Relevance
“…The electric fields administered were 4, 6.5, 10, and 15 kV/cm. The generator consisted of a 10-ohm pulse-forming network (five 50-ohm cables in parallel) and a spark gap in atmospheric air as a nanosecond closing switch (16). Post-pulse, the cell suspension was removed from the nsPEF cuvette and assayed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric fields administered were 4, 6.5, 10, and 15 kV/cm. The generator consisted of a 10-ohm pulse-forming network (five 50-ohm cables in parallel) and a spark gap in atmospheric air as a nanosecond closing switch (16). Post-pulse, the cell suspension was removed from the nsPEF cuvette and assayed.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that nsPEF treatment increased apoptosis signaling mechanisms in both Jurkat and HL-60 cells through assays for caspase activation, annexin binding, and cytochrome c localization (16). Other studies using electric fields weaker than those that induce apoptosis have been shown to cause a proliferative effect on cells.…”
mentioning
confidence: 99%
“…They provide a new approach for physically targeting intracellular organelles with many applications, including the initiation of apoptosis in cultured cells [12][13][14] and tumors [6], enhancement of gene transfection efficiency [13,14], and inhibiting tumor growth [6]. During the past year, we have treated over 300 murine melanomas in 120 mice with 40 kV/cm electric field pulses 300 ns in duration with dramatic results.…”
Section: Introductionmentioning
confidence: 99%
“…Increased permeabilization of the plasma membrane, typically demonstrated by measuring propidium iodide (PI) uptake, due to nsPEFs was delayed compared to traditional electroporation [5,6], indicating that it was an indirect effect. These nsPEFs induced cellular calcium release [7,8] and apoptosis in cells [9,10] or tumors [11,12]. These effects appeared to be due to the charging of interior organelle membranes and the ensuing creation of nanopores.…”
mentioning
confidence: 99%